Sixty days and counting - Robinson, Kim Stanley 1952- (Bantam Books, 2007)
In the conclusion of a trilogy that began with Forty Signs of Rain and Fifty Degrees Below, humankind races against time to prevent or control the repercussions of a series of international disasters, including global warming and environmental instability, before it is too late.
Keywords: Klimaänderung; Global warming -- Fiction; Climatic changes -- Fiction; Scientists -- Fiction; Presidents -- Fiction; Legislators -- Fiction; Washington (D.C.) -- Fiction; Didactic fiction; Suspense fiction